Implementation of Mayor Rules Number 20 Years 2010 about City Worthy of Children Policy with Village Friendly with Children’s Approach in Sendangguwo Village, Tembalang District, Semarang City - Rama Duluber; Budi Puspo Priyadi (Journal of Public Policy and Management Review, 2018)
Implementation of Mayor Rules Number 20 Years 2010 about City Worthy of Children Policy with village friendly with children approach is an action to create the environment which could ensure the children’s right which is implemented by all stakeholders, start from Government, society and privat sector. The purpose of this research is to describe how is Implementation of Mayor Rules Number 20 Years 2010 about City Worthy of Children Policy in Sendangguwo Village, Tembalang Disrict in Semarang City which can be rated through village friendly with children’s indicators based on Pasal 4 scope, which cover the preparation and implementation of the policy. Researcher also some factors which influence the policy implementation in Van Meter and Van Horn model theory and taking 4 variabels from 6 variabels. The methods of this research is using descriptive-qualitative type. The result of the Implementation of Mayor Rules Number 20 Years 2010 about City Worthy of Children in Sendangguwo Village, Tembalang District in Semarang City is still be found some obstacles in some field of children’s right based on indicators which has been determined. The supporting factors in this policy are standard and purpose variable, relation between organizations and social, economy and political condition. On the other hand, the inhibitors factors is the resources that must be improved from quantity and quality side.